F35 The striatum in time production: the model of Huntington's disease in longitudinal study. (12th September 2022) - Lemoine, Laurie; Lunven, Marine; Fraisse, Nicolas; Youssov, Katia; Bapst, Blanche; Morgado, Graça; Reilmann, Ralf; Busse, Monica; Craufurd, David; Rosser, Anne; Gardelle, Vincent de; Bachoud-Lévi, Anne-Catherine
Abstract : The processing of temporal durations ranging from hundreds of milliseconds to minutes, called interval timing, is anatomically linked to the striatum. Patients with Huntington's disease (HD) exhibit striatal degeneration and a deficit in time perception, but whether this deficit extends to time production remains unclear. Clinically, whether this deficit may be a marker of HD before the apparition of symptoms (Pre-HD) or of the longitudinal decline of HD patients is also an important question. In the present study, we tested 101 HD patients at an early stage, 31 Pre-HD and 69 healthy controls in a simple task in which they had to produce durations from 4 to 10 seconds. We found a clear deficit in temporal production for HD patients, whereas Pre-HD performed similar to Controls. For HD patients and Pre-HD participants, task performance was correlated with grey matter volume in the amygdala and caudate, bilaterally. These results confirm that the striatum is involved in interval timing not only in perception but also in production, in accordance with the unified model of time processing. Finally, when retested twelve months later, the deficit of HD patients remain stable, although striatal degeneration was more pronounced. Thus, the simple, short and language-independent temporal production task may be a useful clinical tool to detect striatal degeneration for patients at early stages of Huntington's disease. However, its usefulness to detect presymptomatic stages or to track the evolution of HD over a year appears limited.